CRESCIMENTO E BIOFIXAÇÃO DE CO2 NO CULTIVO DE CHLORELLA EM FOTOBIORREATOR EM FUNÇÃO DE DOSES DE CARBONO ORGÂNICO - SALLES, Jussara Souza; BINOTTI, Flávio Ferreira da Silva; SALLES, Josiane Souza; FERREIRA, Elen Saturnino; RANDO, Fabiana dos Santos; COSTA, Edilson (ANAIS DO ENIC, 2023)
-